Pengaruh Digitalisasi Proses Bisnis Terhadap Kepuasan Pelanggan Di Teras Caffe - Ahmad Aliyafi (Universitas Madura, 2025)
This study examines the effect of business process digitalization on customer satisfaction at Teras Caffe, Tuban. The study used a quantitative descriptive approach by distributing a structured questionnaire to 18 respondents. The study's findings indicate that the use of digital tools such as online ordering, digital payments, and QR code menus significantly improves customer convenience, service speed, and overall satisfaction. These findings suggest that digital transformation is a critical factor in enhancing service experiences and customer loyalty in small food and beverage businesses.